The Year Ahead: Major Tax Changes for Nonprofits in 2022. Issue 1 (9th December 2021) - Lyerly, Eric
Abstract : Non‐profit organizations have had to adapt to numerous challenges in the last few years; some changes were legislative, while others were related to the COVID‐19 pandemic. Not surprisingly, there are further political and organizational changes on the horizon for 2022.